Research trends and prospects of future direction in Islamic banking market share: A bibliometric analysis and mapping - Fauzi, Finorita; Arief, Mts; Maharani, Anita; Heriyati, Pantri (International Journal of Innovative Research and Scientific Studies, 2025)
Islamic banking and finance have evolved from conceptual underpinnings to a globally diverse and empirically robust discipline. It now stands at a crossroads balancing tradition with innovation, ethical imperatives with risk management, and local Sharia-compliant practices with global financial systems. This study presents a bibliometric analysis of research on the market share of Islamic banking in Indonesia, covering the period from 1985 to 2023. Drawing from 1,500 high-impact documents indexed by Elsevier and Emerald, the analysis maps key trends, influential contributions, and thematic developments in the field. The findings highlight the sector’s evolution amid challenges such as product limitations, public awareness gaps, and regulatory hurdles. As Islamic banking increasingly intersects with sustainable finance and digital innovation, this study offers critical insights into its past trajectory and future prospects. It is the first bibliometric study to focus specifically on Islamic banking market share, providing a valuable reference for scholars, policymakers, and practitioners.